Relationship between IgM deposition in the mesangial region and the prognosis of IgA nephropathy: a single-centre retrospective study - Li Gao; Xuan Zhang; Dongrong Yu; Mengjie Jiang; Can Yu; Xiaohong Li; Qin Zhu (BMC Nephrology)
Abstract Objective The aim of this study was to investigate the prognostic value of mesangial IgM deposition in a long-term follow-up cohort of patients with immunoglobulin A nephropathy (IgAN). Methods A retrospective analysis of clinicopathological data from 774 patients with primary IgAN at Hangzhou Hospital of Traditional Chinese Medicine between January 1, 2016, and December 31, 2018, was conducted. Patients were categorized into end-event and non-end-event groups according to whether they reached the renal composite endpoint, defined as a ≥ 50% decline in eGFR or progression to end-stage renal disease (ESRD). Risk factors for adverse renal outcomes were evaluated via univariate and multivariate Cox regression models. Patients were further divided into three groups on the basis of IgM deposition levels in the glomerular mesangial area: IgM-negative, low (IF < 2+), and high (IF ≥ 2+). Comparative analyses of clinical and histopathological characteristics, along with treatment regimens, were performed across these groups. Results Compared with the IgM-negative and low-deposition groups, the high-IgM deposition group exhibited significantly lower serum albumin and eGFR levels and higher cholesterol, 24-hour urine protein, and blood immunoglobulin M levels. Multivariate Cox regression analysis identified immunosuppressant use as an independent protective factor for IgAN prognosis, whereas low serum albumin, T2 lesions, and nephropathological IgM deposits were recognized as independent risk factors for the 5-year prognosis of patients with IgAN. Kaplan‒Meier survival curves revealed that patients with high IgM deposition had markedly poorer prognoses than those with negative or low IgM deposition. Conclusion In addition to low serum albumin and T2 lesions, IgM deposition in the mesangial region has emerged as an independent risk factor for the 5-year prognosis of patients with IgAN.